2014
DOI: 10.1172/jci72181
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages are required for neonatal heart regeneration

Abstract: Myocardial infarction (MI) leads to cardiomyocyte death, which triggers an immune response that clears debris and restores tissue integrity. In the adult heart, the immune system facilitates scar formation, which repairs the damaged myocardium but compromises cardiac function. In neonatal mice, the heart can regenerate fully without scarring following MI; however, this regenerative capacity is lost by P7. The signals that govern neonatal heart regeneration are unknown. By comparing the immune response to MI in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

37
724
4
8

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 694 publications
(773 citation statements)
references
References 43 publications
37
724
4
8
Order By: Relevance
“…Consistent with previous reports, we demonstrate that neonatal mice have a remarkable ability to recover cardiac function, whereas adult mice have a significantly limited capacity (10)(11)(12)(13)(14). The precise macrophage characterization and lineage tracing studies performed herein show that the injured neonatal heart contains an embryonic-derived lineage of cardiac macrophages that promote cardiomyocyte proliferation and coronary angiogenesis, but produce minimal inflammation.…”
Section: Inhibition Of Monocyte Recruitment Preserves Embryonic-derivedsupporting
confidence: 90%
See 3 more Smart Citations
“…Consistent with previous reports, we demonstrate that neonatal mice have a remarkable ability to recover cardiac function, whereas adult mice have a significantly limited capacity (10)(11)(12)(13)(14). The precise macrophage characterization and lineage tracing studies performed herein show that the injured neonatal heart contains an embryonic-derived lineage of cardiac macrophages that promote cardiomyocyte proliferation and coronary angiogenesis, but produce minimal inflammation.…”
Section: Inhibition Of Monocyte Recruitment Preserves Embryonic-derivedsupporting
confidence: 90%
“…Here, we extend these observations and underscore the emerging concept that distinct macrophage lineages exist within tissues and have different biological roles in maintaining homeostasis, consistent with Ilya Metchnikoff's empirically derived concept of "physiologic inflammation" originally proposed in 1901 (21). The concept that distinct macrophage subsets and lineages populate the injured neonatal and adult heart provides a mechanistic basis to explain why the neonatal and adult heart demonstrate different responses to injury and is consistent with and expands on the findings of Aurora and colleagues (14), who demonstrated that cardiac regeneration in the neonatal heart after myocardial infarction was dependent on macrophages. Furthermore, Aurora and colleagues demonstrate that macrophages isolated from infarcted neonatal hearts express a M2 gene expression profile, whereas macrophages isolated from infarcted P14 hearts display a M1 gene expression profile (14).…”
Section: Inhibition Of Monocyte Recruitment Preserves Embryonic-derivedsupporting
confidence: 84%
See 2 more Smart Citations
“…However, these studies are based on peripheral blood monocytes or CBMs, which further differentiate into macrophages ex vivo. Little is known about tissue macrophages in neonates, due to technical difficulties of their isolation and evaluation, but a recent study demonstrated their unique function during heart tissue regeneration [10].It has been shown that the heterogeneous murine macrophage populations are originating from distinct myeloid lineages. In light of these studies, data obtained from circulating mononuclear phagocytes, CBM or bone marrow derived macrophages might not be representative for tissue macrophages, especially in the neonatal period [5,11,12].…”
mentioning
confidence: 99%